ONE HEALTH approach in a changing world (One Health & Risk Management, 2021)
One Health is a multidimensional concept that encourages the community from interdependent fields (such as human medicine, veterinary medicine, environmental health, ecology, public health and health economics) to work together, since when it comes to global health, everything is interconnected. Therefore, to overcome the nowadays health challenges, many factors require to be addressed together.